Consequences of Pseudo(false) -Participation in Decision-Making by Managers of Iranian Public Organizations - Karimi, Rostam; Shakeri, Roya; Shiri, Ardeshir; Khalili, Karam (Management Strategies and Engineering Sciences, 2023)
False participation in decision-making is a phenomenon that clearly indicates dissatisfaction, inefficiencies, and conflicts in organizations. This fact is especially important in government organizations that have a major responsibility for implementing public services. This research has addressed the conceptual model of false participation in decision-making of managers of Iranian government organizations. The research method is qualitative and based on theme analysis. Semi-structured interviews were used to collect data. The statistical population of this study consisted of experts and experts in the field of human resource management and organizational behavior who could provide valuable information to the researcher. Sampling was carried out using a theoretical method and using purposeful (judgmental) and snowball (chain) techniques, based on which 11 interviews were conducted with experts from government organizations. The results of analyzing the data obtained from the interviews through an open, axial and selective coding process and using Maxqda 2018 software to create a model of the consequences of false participation in managers' decision-making based on thematic analysis, including 49 open codes, 9 concepts and 1 category were extracted. Which includes organizational decline, organizational pessimism, social attrition, organizational tyranny, disorder, inability to participate in non-false, reduced productivity, errors in decisions and reduced organizational creativity and innovation. False participation causes executive decisions in government organizations to be made under the influence of certain interests, instead of based on the opinions and real participation of individuals and groups of stakeholders. This phenomenon not only reduces the effectiveness of decisions and their implementation, but also causes dissatisfaction and disappointment among organizational individuals and society. Originality or value of the article: This article is the first article that has been conducted regarding false participation, especially in government organizations in Iran.